The Utilization of Plantable Paper on Tunas Mobile Application - Rani Aryani Widjono (School of Design Universitas Pelita Harapan, 2022)
The replacement of plastic materials with paper materials is considered to be the best solution to save the current waste problem. People generally think that paper material is more friendly to the environment because it is easy to decompose. However, this assumption circulating in the community has an impact on the level of consumption of paper material being unwise. The concept of the waste life cycle is important to understand in this research. That every waste product resulting from every human activity (including paper waste) must have an uninterrupted cycle continuity at the final disposal site in order to be categorized as a sustainable product. By using Human-Centered Design, this research has several objectives, namely utilizing waste (paper) into paper material that can be used as planting media (plantable paper), (2) packaging the concept of instructional information media about farming in a simple way.